2019
DOI: 10.1186/s12931-019-1195-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bruton’s tyrosine kinase in B-cells and autoreactive IgA in patients with idiopathic pulmonary fibrosis

Abstract: RationaleIdiopathic Pulmonary Fibrosis (IPF) is thought to be triggered by repeated alveolar epithelial cell injury. Current evidence suggests that aberrant immune activation may contribute. However, the role of B-cell activation remains unclear. We determined the phenotype and activation status of B-cell subsets and evaluated the contribution of activated B-cells to the development of lung fibrosis both in humans and in mice.MethodsB-cells in blood, mediastinal lymph node, and lung single-cell suspensions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Correlative studies have shown significantly increased expression of memory B cells, plasmablast and BAFF (B cell-activating factor of the TNF family) in lung tissue and peripheral blood of IPF patients [ 39 , 40 ], where BAFF is considered important for the survival of plasma cells [ 41 ]. In addition, the proportion of T follicular helper cells in the peripheral blood of IPF patients increased significantly [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlative studies have shown significantly increased expression of memory B cells, plasmablast and BAFF (B cell-activating factor of the TNF family) in lung tissue and peripheral blood of IPF patients [ 39 , 40 ], where BAFF is considered important for the survival of plasma cells [ 41 ]. In addition, the proportion of T follicular helper cells in the peripheral blood of IPF patients increased significantly [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Correlative studies have shown significantly increased expression of memory B cells, plasmablast and BAFF (B cell-activating factor of the TNF family) in lung tissue and peripheral blood of IPF patients [39,40], where BAFF is considered important for the survival of plasma…”
Section: Comparison Of B-cell Lineage Transcriptional Estimated Infilmentioning
confidence: 99%
“…Perhaps as a compensatory mechanism, aberrant expansion of ectopic inducible bronchus-associated tissues (iBALT) independently supports the maturation and selection of B cells (CD5 + and CD20 + ) in aged, COPD, and IPF clinical cohorts, in particular those with cigarette smoking history (294)(295)(296). Single cell sequencing and proteomic analysis of lungs and peripheral blood cells from IPF individuals shows strong evidence of B1 and CD38 + CD138 + plasma cells accumulation, while experimental modeling of fibrosis generated strong correlation between the degree of pulmonary fibrosis and B-cell numbers in the germinal center (297)(298)(299)(300). The involvement of B cells in sterile (environmental) injury is not as well-established, aside from allergen induced IgE production in aging asthma cohorts (301).…”
Section: B Cellsmentioning
confidence: 65%
“…Increased BTK expression was found in circulating B cells in a fraction of patients with idiopathic pulmonary fibrosis (IPF; Heukels et al, 2019). However, BTKi showed divergent effects in bleomycin mouse models for pulmonary fibrosis, likely due to off-target effects and multi-kinase inhibition (Gu et al, 2018;Sun et al, 2020).…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%